Konservatisme Akuntansi, Value Velevance dan Discretionary Accruals: Implikasi Empiris Model Feltham-Ohlson (1996) - Sekar Mayangsari; Wilopo Wilopo (The Indonesian Journal of Accounting Research, 2013)
This study documents evidence on the valuation effects of accounting conservatism in context of the Feltham-Ohlson (1996) model. This study investigates whether managers manage reported earnings under conservatism. Recent accounting research finds that the discretionary accruals component of earnings communicates managers’ private information to investor and can use as a tool for detecting earnings management. We find, first,that goodwill (the difference between market and book value of equity) is a function of abnormal operating earnings and beginning operating earnings. Our test results support the implication of FO model that the effect of abnormal operating earnings on goodwill increases with operating cash receipts persistence. Second, we find there is an earnings management in  firm  that implement conservatism. Third, interaction between discretionary accruals and bonus plan, debt covenant and political cost, can effect firm’s value.